When Backward Integration by a Dominant Firm Improves Welfare - Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper studies the welfare consequences of a vertical merger that raises rivals costs when downstream competition is à la Cournot between firms with constant asymmetric marginal costs. The main result is that such a vertical merger can nevertheless improve welfare if it involves a downstream firm whose cost is low enough. This is because by raising the input price paid by the non-merging firms the merger thereby shifts production away from those relatively inefficient producers in favor of the more efficient firm. However there is a tradeoff between the gain in productive efficiency and the loss in consumers surplus caused by a higher downstream price which follows a higher input price. It is also shown, through an example, that this result extends to price competition with differentiated products.
Keywords: 330; foreclosure; raising rival costs; Cournot; welfare; asymmetric costs